2012
DOI: 10.1111/j.1399-3054.2012.01663.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cambial activity in relation to environmental conditions: understanding the role of temperature in wood formation of trees

Abstract: The timing of cambial reactivation plays an important role in determination of the amount and quality of wood and the environmental adaptivity of trees. Environmental factors, such as temperature, influence the growth and development of trees. Temperatures from late winter to early spring affect the physiological processes that are involved in the initiation of cambial cell division and xylem differentiation in trees. Cumulative elevated temperatures from late winter to early spring result in earlier initiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
157
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 240 publications
(185 citation statements)
references
References 53 publications
9
157
0
1
Order By: Relevance
“…Rising temperatures may induce earlier cambial reactivation (40), resulting in both a higher rate of xylem cell production and a longer duration of cambial growth, which in principle should increase ring width (41). This was not the case for Siberia, however, where an earlier onset of cambial activity may be associated with an increased risk of frost damage to the cambium (40).…”
Section: Resultsmentioning
confidence: 99%
“…Rising temperatures may induce earlier cambial reactivation (40), resulting in both a higher rate of xylem cell production and a longer duration of cambial growth, which in principle should increase ring width (41). This was not the case for Siberia, however, where an earlier onset of cambial activity may be associated with an increased risk of frost damage to the cambium (40).…”
Section: Resultsmentioning
confidence: 99%
“…Both external and internal factors control xylogenesis (Wilson 1984;Aloni 2013) and are likely involved in the regulation of its timing (Lachaud et al 1999). Among these factors, temperature is expected to be a major cue for the phenology of xylogenesis, considering its influence on cell structure (Begum et al 2012) and on basic processes, such as the modulation of the division rate of cambium initials (Begum et al 2013) and the regulation of gene expression related to active auxin transport (Schrader et al 2003).…”
Section: The Phenology Of Wood Formationmentioning
confidence: 99%
“…Moreover, the resumption of cambial activity can be triggered during late winter by an artificial heating of tree stems (Oribe et al 2003;Begum et al 2007Begum et al , 2010. Interestingly, this artificial resumption of cambial activity can only be triggered during the ecodormancy phase of cambium tissue (referred to as the "quiescent phase" in Oribe and Kubo 1997;Begum et al 2013) after the chilling requirement has been fulfilled during endodormancy (referred to as the "rest phase" in Little and Bonga 1974;Begum et al 2013). However, the influence of temperature on cambium activity remains equivocal.…”
Section: The Phenology Of Wood Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Feliksik et al (2007) found that cold winters and low air temperature in early spring, as well as low amount of precipitation during the summer (June-July), were the most important meteorological elements inhibiting the radial growth of black locust. The air temperature from late winter to early spring affects the physiological processes involved in the initiation of cambial cell production and in differentiation of xylem cells in the tree (Begum et al, 2013). Importantly, premature initiation of cambial activity increases the risk of damage to biomass growth because of a sudden drop in air temperature below the physiological tolerances of the tree.…”
Section: Raspravamentioning
confidence: 99%